2014
DOI: 10.1093/imrn/rnu060
|View full text |Cite
|
Sign up to set email alerts
|

 -Galois Theory of Linear Difference Equations

Abstract: We develop a Galois theory for systems of linear difference equations with an action of an endomorphism σ. This provides a technique to test whether solutions of such systems satisfy σ-polynomial equations and, if yes, then characterize those. We also show how to apply our work to study isomonodromic difference equations and difference algebraic properties of meromorphic functions. IntroductionInspired by the numerous applications of the differential algebraic independence results from [34], we develop a Galoi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 43 publications
1
37
0
Order By: Relevance
“…Thus we have shown that (33) is equivalent over C(x) to σ(Z) = A 0 Z with some constant invertible matrix A 0 . To complete the proof of Theorem 13 for case 2Q, apply the same gauge transformation to σ 2 (Y ) = B 2 (x)Y to obtain σ 2 (Z) =B 2 (x)Z.…”
Section: Proof Of Theorem 13: Case 2qmentioning
confidence: 85%
“…Thus we have shown that (33) is equivalent over C(x) to σ(Z) = A 0 Z with some constant invertible matrix A 0 . To complete the proof of Theorem 13 for case 2Q, apply the same gauge transformation to σ 2 (Y ) = B 2 (x)Y to obtain σ 2 (Z) =B 2 (x)Z.…”
Section: Proof Of Theorem 13: Case 2qmentioning
confidence: 85%
“…In the applications of the PPV theory, it is often useful to know whether any of the solutions to (12) are Π-transcendental (see e.g. Arreche, 2013;Hardouin, 2008;Hardouin and Singer, 2008;Ovchinnikov and Wibmer, 2015). We denote by D := F •Π the Lie vector space of parametric derivations obtained by taking the F -linear span of Π.…”
Section: Criteria For Differential Transcendencementioning
confidence: 99%
“…The dependence of a full set of solutions of a linear functional equation with respect to a discrete parameter is considered in [8], [9] and [18]. Due to the intrinsic difficulty of difference algebra, the proofs, but also sometimes the statements, are more complicated than in the analogous continuous theory.…”
Section: Introductionmentioning
confidence: 99%